Sediment contamination in two German estuaries : a biomarker-based toxicity test with the ragworm Hediste diversicolor under intermittent oxygenation - Duy Nghia Pham and Safia El Toum and Raphaëlle Martineau and Susanne Heise and Inna M. Sokolova (Environmental research : ER ; a journal of environmental sciences, 2024)
Toxicity testing is an important tool for risk assessment of sediment contamination in estuaries. However, there has been a predominant focus on fitness parameters as toxic endpoints and on crustaceans as test organisms, while effects at the sub-organismal level and on other benthic taxa have received less attention. Also, interactions between sediment contamination and natural stressors such as oxygen are often neglected in traditional toxicity tests. Here we conducted a toxicity test of sediments from the Elbe and Oder (Odra) estuaries under three weeks of continuous and intermittent oxygenation, using biomarkers in an annelid, the ragworm Hediste diversicolor. Contaminated sediments affected worm survival and some biomarkers of antioxidant defense, electrophilic stress, and energy status with response ratios of above 20%. Toxic effects were most pronounced in sediments from the upper Elbe estuary, which contained high levels of heavy metals and organic chemicals. Oxygen regimes hardly changed the sediment effects, suggesting the robustness of the biomarker-based toxicity test with ragworms.
Keywords: Additive interaction; Bioenergetics; Field sediments; Hypoxia; Pollution; Polychaete